Blended learning for developing effective virtual teams: a proposed intervention format - Cristiano Ghiringhelli; Alessandra Lazazzara (European Alliance for Innovation (EAI), 2016)
The aim of this exploratory study was to develop a blended learning approach to fostering the skills and competencies required by leaders and members of international virtual teams. Three levels of analysis were brought to bear in designing the proposed intervention format: first, the factors likely to influence the effectiveness of a virtual team; second, the needs and challenges related to the early stages of the virtual team membership; third, the role of the human resource function in promoting - via training and development programmes - the knowledge and skills needed for virtual teams to be successful. The research questions included: What are the perceived benefits and challenges associated with the early stages of virtual collaboration? What factors must be carefully defined and managed when running a virtual team? What training needs are perceived by inexperienced virtual team members? How can training and development initiatives contribute to the effectiveness of virtual teams? A qualitative approach based on the model developed by Bal & Gundry was used to analyse data from five interviews with virtual team members at Nielsen TAM Italy. The outcomes informed the proposed blended training programme.